Developing Learning Strategies to Improve Students' Learning Motivation - Nur’aini; Sumianti (Golden Ratio of Social Science and Education, 2025)
This study explores the development of effective learning strategies aimed at enhancing students' learning motivation. Employing a systematic literature review (SLR) method, this research analyzes scholarly works published in the last ten years. The findings reveal that active, contextual, and student-centered approaches such as Problem-Based Learning, Project-Based Learning, and collaborative learning can significantly increase students’ intrinsic and extrinsic motivation. Furthermore, integrating technology through digital media, e-learning, and gamification improves students’ engagement and learning satisfaction. The application of Keller’s ARCS motivational model, Gardner’s theory of Multiple Intelligences, and Vygotsky’s sociocultural approach provides a comprehensive theoretical foundation for designing motivational learning strategies. The study emphasizes the importance of teacher competence, technological adaptation, and supportive learning environments. This research contributes theoretically and practically to education by offering a conceptual framework for designing strategies that improve student motivation in the modern learning context.